Supporting Children and Their Families in Gauteng Public Schools: The Roles of School Social Workers - Gift Khumalo; Nolwazi Ngcobo; Mbongeni Shadrack Sithole (Social Sciences, 2025)
School social work practice in the South African context is a growing field; however, there is limited research regarding the roles and responsibilities of school social workers, particularly in the Gauteng province. This province is unique in that school social workers are employed by multiple institutions, including individual schools and the education and social development departments. This study aimed to explore and describe the roles and responsibilities of school social workers in the Gauteng province, recognizing them as critical specialists in addressing learners’ psychosocial needs within school settings. An explorative qualitative design was used in this study. Data were collected from 22 purposively selected participants, comprising school social workers, supervisors, and provincial managers of school social work programs. Semi-structured interviews were conducted to collect data, and thematic analysis was employed to identify themes. The findings revealed context-specific roles of school social workers, including the creation of conducive teaching and learning environments, advocacy for social justice and child protection, conducting interviews and psychosocial assessments, providing counseling and trauma debriefing, conducting home visits and offering family services, removing abused learners from harmful environments, including their respective homes, and providing parental skills training and support. As a conclusion, this study highlights the need for standardized national and provincial guidelines to formalize and support school social work practice. It is recommended that the identified roles be incorporated into future practice frameworks. Furthermore, it is suggested that a uniform assessment tool be developed to promote consistency and guide school social workers in the initial evaluation processes.